Digital Banking Transformation Through Cooperation with Fintech Startups in Ukraine - Sophia Lobozynska; Ulyana Vladychyn; Iryna Skomorovych (Finanse i Prawo Finansowe, 2023)
The purpose of the article/hypothesis: Is to identify the peculiarities of Fintech startups activities, to track trends and perspectives of interaction between classic banks and Fintech companies, as well as to research the activities of neobanks and formulate proposals for improving the Fintech ecosystem in Ukraine with the aim of providing quality digital financial services to various categories of consumers.